Ambiguous temperature difference in aerodynamic levitation process: Modelling, solving and application. Issue 8 (August 2019) - Ge, Xuan; Xu, Xiaowei; Hu, Qiaodan; Lu, Wenquan; Yang, Liang; Cao, Sheng; Xia, Mingxu; Li, Jianguo
Abstract: The aerodynamic levitation provides an efficient technique for the research on thermophysical properties and solidification behavior of refractory materials. However, there is a nonnegligible temperature differences across sample, causing unexpected uncertainty of measurement, such as, thermal expansivity and undercooling limit. We establish thermal filed model with properly simplified boundary condition, and derive quantitative expressions of this ambiguous temperature difference. Here we show that the temperature difference not only related to the average temperature, relative size and thermal conductivity of sample, but significantly influenced by the rotation pattern of sample. A huge temperature differences is almost inevitable when the sample with low thermal conductivity and high melting point is smelted in stationary suspension pattern, however, a drastically reduction of temperature difference can be fulfilled by simply making the sample rotation in up to down pattern. The thermal filed simulation was used to confirm the validity of these theoretical expressions. This work shed light on temperature difference in aerodynamic levitation. Based on this work, one can simply estimate the extent of temperature difference across the sample, and regulated that conveniently if needed, which benefit for novel material preparation and solidification mechanism study based on this technique.